Prevalence of respiratory pathogens among hospitalised patients with acute respiratory infection during and after the COVID-19 pandemic in Shijiazhuang, China - Zheng, Pan-pan; Zhao, Ya-nan; Wang, Zhi-kai; Wang, Min-zhen; Li, Rong; Zhang, Jing; Li, Nan; Zhang, Zi-feng; Rong, Rui-juan; Sun, Yi-chan; Liu, Zan-chao (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundThe COVID-19 pandemic and the resulting non-pharmaceutical interventions (NPIs) have led to changes in the epidemiology of other respiratory pathogens. This study was conducted to explore the epidemiological characteristics of 13 respiratory pathogens, including 11 respiratory viruses and 2 non-classical microorganisms, in hospitalised patients with acute respiratory tract infections (ARTIs) and to compare the prevalence of respiratory pathogens during and after the COVID-19 pandemic.MethodsWe conducted a single-centre retrospective study involving 8979 patients with ARTIs in Shijiazhuang City from December 2019 to December 2023. The GeXP analysis platform and multiple reverse transcription–PCR (mRT–PCR) technology were used to simultaneously detect 13 respiratory pathogens. The ARIMA model was constructed to predict the pathogen detection rate in each quarter of Shijiazhuang City in the next 2 y.ResultsAmong the 8979 patients, 4169 (46.43%) tested positive for respiratory pathogens. The total pathogen detection rate rebounded in the year after the COVID-19 pandemic. After the COVID-19 pandemic, the positive rates in men were slightly higher than those in women and the positive rates in spring and winter were significantly higher than those in summer. The dominant pathogens during the COVID-19 pandemic were Influenza A viru (InfA; 24.08%) and Human Rhinovirus (HRV; 21.77%), and after the COVID-19 pandemic were InfA (27.92%) and H3 (21.17%). During the COVID-19 pandemic, InfA and HRV frequently occurred in all age groups. After the COVID-19 pandemic, InfA and Seasonal Influenza virus H3N2 (H3) frequently occurred in all age groups.ConclusionsA series of NPIs introduced by the Chinese government during the COVID-19 pandemic had a significant impact on acute upper respiratory pathogenic infections. After the withdrawal of the NPIs, the spectrum of respiratory pathogens changed.